Caracterização molecular do fitoplasmas do grupo 16SrIII e um novo fitoplasma do grupo 16SrVII em Vernonia brasiliana - Silva, Jaqueline Manzatti da (2014)
Phytoplasmas are prokaryotic cell wall and mandatory phloem parasites, disease causing in various agronomic crops. Plant Vernonia spp., Asteraceae family, with symptoms of chlorosis and overbudding were found in pastures in the city of Patos de Minas, Minas Gerais, and subsequently occurring in plants in pastures of Piracicaba, São Paulo and Maringa, Parana. The objective of this study was to detect and identify phytoplasmas possibly associated with these symptoms. For this, total DNA of the plants was subjected to double PCR assay employing universal primers for specific detection and identification phytoplasms primers. Products amplified by the universal primers revealed the presence of 42.66% of phytoplasms collected in plants. The use of specific primers showed the occurrence of phytoplasmas affiliated to group 16SrIII. Virtual RFLP Analyses based on enzymatic digestion of the 16S rDNA nucleotide sequence and phylogenetic analysis allowed classifying these as members of phytoplasms 16SrIIII-B and J-16SrIII subgroups. Also identified a phytoplasma group 16SrVII, which was quite distinct from representatives of other subgroups so far described for this group. Observations at scanning electron microscope and transmission revealed the presence of corpuscles typical pleomorphic phytoplasmas in the phloem of symptomatic plants, confirming the results of molecular detection.